Modeling the daily activities of breeding colonial seabirds: Dynamic occupancy patterns in multiple habitat patches - Andrea L. Moore; Smruti P. Damania; Shandelle M. Henson; James L. Hayward (Mathematical Biosciences and Engineering)
We constructed differential equation models for the diurnal abundance anddistribution of breeding glaucous-winged gulls (Larus glaucescens)as they moved among nesting and non-nesting habitat patches. We used timescale techniques to reduce the differential equations to algebraic equationsand connected the models to field data. The models explained the data as afunction of abiotic environmental variables with $R^{2}=0.57$. A primarygoal of this study is to demonstrate the utility of a methodology that canbe used by ecologists and wildlife managers to understand and predict dailyactivity patterns in breeding seabirds.